THE RELATIONSHIP BETWEEN WORKING BEHAVIOR AND THE INCIDENCE OF TYPE II DIABETES MELLITUS OF WORKERS WITH THE SNEHANDU THEORY - Ninin Nuryantini Farid; Bagus Pratama Suwardono (Universitas Airlangga, 2021)
ABSTRACTThere are two types of Diabetes Mellitus (DM), namely Type I DM and Type II DM. Type II DM is caused by the inability of the body to respond to insulin that is produced by the pancreas, thus resulting in an increase in blood glucose levels. Eleven out of twenty workers at the Faculty of Public Health, Universitas Airlangga suffered from Type II DM. Observational research with a quantitative approach was conducted through a cross-sectional approach. The population selected was 89 workers at the faculty. The samples were randomly selected with the characteristics of having more than 45 years of age. There were significant variables between working behavior and the incidence of Type II DM including work, last education, and social support. Furthermore, there were insignificant variables between working behavior and the incidence of Type II DM including gender, age, family members, frequency of exercise, behavior intention, personal autonomy, accessibility to information, and action situation. In conclusion, individual’s latest education, employment, and social support had a significant relationship with exercise behavior and the incidence of Type II DM. Keywords: physical exercise, diabetes mellitus, wokers at FKM Universitas Airlangga